Social ethics and normative economics essays in honour of Serge-Christophe Kolm - Fleurbaey, Marc.; Salles, Maurice; Weymark, John A.; SpringerLink (Berlin ; Heidelberg ;New York Springer, 2011)
This collection of thirteen essays on social ethics and normative economics honouring Serge-Christophe Kolm's seminal contributions to this field addresses the following questions: How should the public sector price its production and services? What are the normative foundations of criteria for comparing distributions of riches and advantages? How should intergenerational social immobility and inequality in circumstances be measured? What is a fair way to form partnerships? How vulnerable to manipulation is the Lindahl rule for allocating public goods? What are the properties of Kolm's ELIE tax proposal? Would the addition of EU-level income taxes enhance equity? How should we compare different scenarios for future societies with different population sizes? How can domain conditions in social choice theory be justified using Kolm's epistemic counterfactuals? How can Kolm's distributive liberal contract be implemented? What are the implications of norms of reciprocity for the organization of society? The answers to these questions give major insight into the state-of-the-art of social ethics and normative economics and are thus an indispensable source for researchers in both of these fields.
Social Ethicsand Normative Economics; Preface; Contents; Contributors; An Introduction to Social Ethics and Normative Economics; Kolm as a Contributor to Public Utility Pricing, Second-Best Culture, and the Theory of Regulation; Public Utility Pricing and Capacity Choice with Stochastic Demand; Bidimensional Inequalities with an Ordinal Variable; Inequality of Life Chances and the Measurement of Social Immobility; Partnership, Solidarity, and Minimal Envy in Matching Problems; Borrowing-Proofness of the Lindahl Rule in Kolm Triangle Economies; When Kolm Meets Mirrlees: ELIE Kolm's Tax, Tax Credit, and the Flat TaxPositional Equity and Equal Sacrifice: Design Principles for an EU-Wide Income Tax?; Comparing Societies with Different Numbers of Individuals on the Basis of Their Average Advantage; On Kolm's Use of Epistemic Counterfactuals in Social Choice Theory; Optimal Redistribution in the Distributive Liberal Social Contract; Reciprocity and Norms; Scientific Publications of Serge-Christophe Kolm
Electronic reproduction.
Keywords: Economics -- Moral and ethical aspects; Kolm, Serge-Christophe.; Electronic books